Some Notes on Dual Spherical Curves - Yayli, Yusuf; Saracoglu, Semra (Journal of Informatics and Mathematical Sciences, 2011)
In this study, by investigating one parameter spherical motion in $\mathbb{D}^{3}$ with two different kinds of dual indicatrice curves, we have obtained the ruled surfaces that correspond to tangent, principal normal and binormal indicatrices of the dual curve are developable. Furthermore, it can be easily seen that this study gives a link between the classical surface theory and dual spherical curves on the dual unit spheres.